Trends in Tariff Reforms and Trends in the Structure of Wages - Sebastián Galiani; Guido Porto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2011)
This paper provides new evidence on the impacts of trade reforms on wages. We first introduce a model of trade that combines a non-competitive wage setting mechanism due to unions with a factor abundance hypothesis. The predictions of the model are then econometrically investigated using Argentine data. Instead of achieving identification by comparing industrial wages before and after one episode of trade liberalization, our strategy exploits the recent historical record of policy changes adopted by Argentina: from significant protection in the early 1970s, to the first episode of liberalization during the late 1970s, then back to a slowdown of reforms during the 1980s, and finally to the second episode of liberalization in the 1990s. These swings in trade policy represent broken trends in trade reforms that we can compare with observed trends in wages and wage inequality. We use unusual historical data sets of trends in tariffs, wages, and wage inequality to examine the structure of wages in Argentina and to explore how it is affected by tariff reforms. We find that i) trade liberalization, ceteris paribus, reduces wages; ii) industry tariffs reduce the industry skill premium; iii) conditional on the structure of tariffs at the industry level, the average tariff in the economy is positively associated with the aggregate skill premium. These findings suggest that the observed trends in wage inequality in Latin America can be reconciled with the Stolper-Samuelson predictions in a model with unions.
Keywords: F14; F16; 330; Trade liberalization; Stolper-Samuelson; Wage inequality; non-competitive wages and unions; Handelsliberalisierung; Zollpolitik; Lohn; Lohnstruktur; Argentinien